MAHASISWA SEBAGAI AGEN TRANSFORMASI DALAM PENDIDIKAN PERSPEKTIF MUHAMMAD IQBAL - Ardita Sindy; Melikai Jihan El-Yunusi (Sekolah Tinggi Ilmu Tarbiyah Al - Ibrohimy Bangkalan, 2023)
Education is a means of developing character and critical thinking. In this respect education promotes a deep understanding of morality and science. Students as individuals and social beings have personal rights to be respected by society and social obligations to be fulfilled. Thus, the aim of this research is to analyze the individual and social in achieving positive transformation in education in society. Because students as agents of change are fighting for improvement in the education system. As for the research method, this is a library reasearch method with a qualitative descriptive approach that comes from journals, books, and so on. The results of this study explain that students can be agents of transformation by integrating the knowledge and moral values they have acquired from education into real actions that help society. Students can it by expressing their aspirations, helping to improve the quality of education and creating an enabling environment for learning.